Correlation of normal lung density changes with dose after stereotactic body radiotherapy (SBRT) for early stage lung cancer. (May 2020) - Al Feghali, Karine A.; Wu, Qixue (Charles); Devpura, Suneetha; Liu, Chang; Ghanem, Ahmed I.; Wen, Ning (Winston); Ajlouni, Munther; Simoff, Michael J.; Movsas, Benjamin; Chetty, Indrin J.
Highlights: There is a strong positive correlation between HU changes in the peri-tumoral region and the grade of RP after SBRT for NSCLC. V20, MLD, and gEUD are significantly correlated with RP grade. Relative to model-based methods, PB algorithms overestimate mean peri-tumoral dose. Relative to model-based methods, PB algorithms show a 10–15% volume displacement of the high-dose region. Abstract: Background and Purpose: To investigate the correlation between normal lung CT density changes with dose accuracy and outcome after stereotactic body radiation therapy (SBRT) for patients with early stage non-small-cell lung cancer (NSCLC). Materials and Methods: Thirty-one patients (with a total of 33 lesions) with non-small cell lung cancer were selected out of 270 patients treated with SBRT at a single institution between 2003 and 2009. Out of these 31 patients, 10 patients had developed radiation pneumonitis (RP). Dose distributions originally planned using a 1-D pencil beam-based dose algorithm were retrospectively recomputed using different algorithms. Prescription dose was 48 Gy in 4 fractions in most patients. Planning CT images were rigidly registered to follow-up CT datasets at 3–9 months after treatment. Corresponding dose distributions were mapped from planning to follow-up CT images. Hounsfield Unit (HU) changes in lung density in individual, 5 Gy, dose bins from 5 to 45 Gy were assessed in the peri-tumoral region. Correlations between HU changes in various normal lung regions, dose indices (V20, MLD, generalized equivalent uniform dose (gEUD)), and RP grade were investigated. Results: Strong positive correlation was found between HU changes in the peri-tumoral region and RP grade (Spearman's r = 0.760; p < 0.001). Positive correlation was also observed between RP and HU changes in the region covered by V20 for all algorithms (Spearman's r ≥ 0.738; p < 0.001). Additionally, V20, MLD, and gEUD were significantly correlated with RP grade ( p < 0.01). MLD in the peri-tumoral region computed with model-based algorithms was 5–7% lower than the PB-based methods. Conclusion: Changes of lung density in the peri-tumoral lung and in the region covered by V20 were strongly associated with RP grade. Relative to model-based methods, PB algorithms over-estimated mean peri-tumoral dose and showed displacement of the high-dose region, which correlated with HU changes on follow-up CT scans.